Developing a Website Pocket Book with PjBL to Enhance UI/UX Basic Competence - Pratiwi, Nawang Indar; Ekohariadi (Universitas Negeri Surabaya, 2025)
The advancement of information and communication technology has provided opportunities to develop innovative and interactive learning media. One of the main challenges in teaching UI/UX material to 11th – grade DKV student at SMK PGRI 2 Sidoarjo is how to deliver the material effectively so that student can master the basic competencies. A web-based pocketbook learning media with the Project Based Learning (PjBL) model is expected to be a solution to enhance studentd understanding of UI/UX subjects in the 11th-grade DKV class at SMK PGRI 2 Sidoarjo. This research employs the Research and Development (R&D) method using the ADDIE model. The result show that the use of a web-based pocketbook media with the PjBL model successfully improved students’ basic competencies in UI/UX material. Student demonstrated improvement in their understanding of basic UI/UX concept, user interface design skill, and collaboration abillities. Additionaly, this media received positive feedback from both students and teachers, particularly in terms of accesibility, interactivity, and the availability of easily accesible material throught the web platform. The use of the web-based pocketbook learning media proved effective in improving student learning outcomes, especially in UI/UX material that requires a practical and interactive approach. The applied PjBL model provided students with the opportunity to learn through hands-on experience in working on projects, which ultimately enhanced their concepts and skills.